The use of the Internet and the changing pattern of influence in advertising agency selection teams. - Cheong, Adelyn Lye Kuen. (2008)
This research identifies the impact of the Internet on the buying size and influential structure of the buying centres in organisations. This study is based on the selection of advertising agencies and with specific respect to the two major players in such a buying centre, the marketing and general manager.